ВЛИЯНИЕ ТЕРАПИИ ПСИХИЧЕСКИХ РАССТРОЙСТВ ПРИ ХРОНИЧЕСКОЙ ОБСТРУКТИВНОЙ БОЛЕЗНИ ЛЁГКИХ НА ПРОЯВЛЕНИЯ ОСНОВНОГО ЗАБОЛЕВАНИЯ - Н. В. Обухов; В. И. Трофимов; В. И. Крылов (SINAPS LLC, 2014)
The prevalence of psychopathological syndromes in patients with chronic obstructive pulmonary disease (COPD) is estimated in this article. The impact of the disease on comorbid psychiatric disorders severity and impact of their treatment on the COPD symptoms are considered. 5 most frequent psychiatric syndromes were identified. The efficacy against mental disorders and symptoms of underlying disease for individual pathogenetic psychotherapy and therapy in the group for improving the quality of life in patients with COPD is shown.